Model Predictive Control Design for SISO LTI system subjected to bounded constraints (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper Model Predictive Control (MPC)for SISO LTI system is considered. MPC emanates fromdynamicoptimisation where a dynamical system is controlled while minimising the associated performance index andsatisfying all the constraints.Using current measurement of states (if all states are available for measurement elsestateobserver is used) a predicted plant model is obtained on a prediction horizon (N) and using this predicted plant modelwe get the predicted performance index which is minimized to get a future control sequence. The first component of thecontrol sequence is used while rest gets discarded and the at the next instance the whole process is repeated. In thispaper a LTI SISO system is subjected to constraints on both input and output is considered. Simulation results verify theefficacy of the designed algorithm.